Innovation activity in Ukraine: state, problems and legal framework improving perspectives - Shovkalіuk, V.; Chaika, D. (Наука, технології, інновації, 2017)
Ukraine has rich natural resources and is a leading global manufacturer of number of agricultural and industrial goods. However, the innovation level of companies and their production of goods with high added value is low. Article provides view Ministry of Education and Science of Ukraine initiatives of necessary changes in the regulatory and institutional field that regulates innovation. Україна володіє багатими природними ресурсами та є провідним світовим виробником низки аграрних і промислових товарів. Але рівень інноваційного розвитку її підприємств і виробництва ними товарів із високим ступенем доданої вартості вкрай низький. У статті надано думку спеціалістів МОН щодо необхідних нормативних та інституційних змін у сфері інноваційної діяльності. Украина обладает богатыми природными ресурсами и является ведущим мировым производителем ряда аграрных и промышленных товаров. Но уровень инновационного развития ее предприятий и производства ими товаров с высокой степенью добавленной стоимости крайне низок. В статье приведены мнения специалистов МОН о необходимых нормативных и институциональных изменениях в сфере инновационной деятельности.